2021
DOI: 10.3389/fpls.2021.733245
|View full text |Cite
|
Sign up to set email alerts
|

The Flower-Infecting Fungus Ustilaginoidea virens Subverts Plant Immunity by Secreting a Chitin-Binding Protein

Abstract: Ustilaginoidea virens is a biotrophic fungal pathogen specifically colonizing rice floral organ and causes false smut disease of rice. This disease has emerged as a serious problem that hinders the application of high-yield rice cultivars, by reducing grain yield and quality as well as introducing mycotoxins. However, the pathogenic mechanisms of U. virens are still enigmatic. Here we demonstrate that U. virens employs a secreted protein UvCBP1 to manipulate plant immunity. In planta expression of UvCBP1 led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Recently, the RNAi‐based approach host‐induced gene silencing (HIGS) was developed as an alternative strategy to control fungal diseases. In this strategy, siRNAs targeting selected genes of the invading pathogen are produced by transgenic host plants to silence fungal genes during infection (Chen et al ., 2022c ; Li et al ., 2021a , b ; Machado et al ., 2018 ; Nowara et al ., 2010 ). For example, HIGS of FgChs3b , FgCYP51 , FgSGE1 , FgFGP1 , or FgSTE12 conferred resistance to Fusarium head blight fungus Fusarium graminearum in wheat ( Triticum aestivum ) (Cheng et al ., 2015 ; Koch et al ., 2013 ; Wang et al ., 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the RNAi‐based approach host‐induced gene silencing (HIGS) was developed as an alternative strategy to control fungal diseases. In this strategy, siRNAs targeting selected genes of the invading pathogen are produced by transgenic host plants to silence fungal genes during infection (Chen et al ., 2022c ; Li et al ., 2021a , b ; Machado et al ., 2018 ; Nowara et al ., 2010 ). For example, HIGS of FgChs3b , FgCYP51 , FgSGE1 , FgFGP1 , or FgSTE12 conferred resistance to Fusarium head blight fungus Fusarium graminearum in wheat ( Triticum aestivum ) (Cheng et al ., 2015 ; Koch et al ., 2013 ; Wang et al ., 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…virens based on genomic analysis (Zhang et al ., 2014, 2021). Recent studies have demonstrated that a number of these effectors play critical roles in infection, including SCRE1, SCRE4, SCRE6, SGP1, UvCBP1, UvPr1a, and UvSec117 (Chen et al ., 2022a,b; Li et al ., 2021a; Qiu et al ., 2022; Song et al ., 2021; Yang et al ., 2022; Zhang et al., 2020; Zheng et al ., 2022). For example, the effector SCRE6 acts as a tyrosine phosphatase that dephosphorylates the negative defence regulator OsMPK6 (MAP Kinase) to enhance its accumulation, thereby inhibiting rice immunity (Zheng et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To verify the functionality of GcR8IP1 signal peptide, plasmids of pSUC2‐GcR8IP1 16aa , pSUC2‐GcR8IP1 26aa , pSUC2‐GcR8IP1 40aa , pSUC2‐Avr1b SP , and pSUC2‐Mg87 N were separately transformed into yeast strain YTK12 and subjected to yeast secretion assay as performed previously (Li et al ., 2021). To further confirm the functionality of GcR8IP1 40aa in secretion, GcR8IP1 40aa ‐GFP was transiently expressed in N. benthamiana leaves and treated with/without 12% (w/v) sucrose solution for 10 min, before observation under a confocal laser scanning microscope (Nikon A1).…”
Section: Methodsmentioning
confidence: 99%
“…SCRE6 functions as a tyrosine phosphatase and dephosphorylates the negative immune regulator OsMPK6, thus stabilizing OsMPK6 and inhibiting rice immunity (Zheng et al ., 2022). The chitin‐binding protein UvCBP1 in U. virens competes with rice chitin receptor OsCEBiP for chitin binding, and thereby subverts pattern‐triggered immunity (Li et al ., 2021). Interestingly, a Ser‐Thr‐rich GPI‐anchored protein (SGP1) in U. virens functions as a PAMP and induces plant immune responses, although the protein is critical for pathogen virulence (Song et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%